2005
DOI: 10.1097/01.psy.0000188569.58998.c8
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Predict CD4 and Viral Load Change in Men and Women With Human Immunodeficiency Virus in the Era of Highly Active Antiretroviral Treatment

Abstract: Objective-Most previous longitudinal studies demonstrating relationships between psychosocial variables and human immunodeficiency virus (HIV) disease progression utilized samples of gay men accrued before the era of highly active antiretroviral treatment (HAART), without including viral load (VL) as an indicator of disease progression or assessing the impact of medication adherence. This study sought to determine whether psychosocial variables would predict both CD4 and VL changes in a diverse sample assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
247
6
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 314 publications
(278 citation statements)
references
References 61 publications
20
247
6
5
Order By: Relevance
“…On the other hand our finding a higher risk of major depression in patients with symptomatic disease short of AIDS is consistent with evidence of increase in depressive symptoms as disease progresses (Lyketsos et al, 1996). The finding that incident major depressive episode was associated with more rapid decline in immune function (CD4+ lymphocyte count) is consistent with evidence that depressive symptoms are associated with more rapid progression of HIV disease (Ironson et al, 2005).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand our finding a higher risk of major depression in patients with symptomatic disease short of AIDS is consistent with evidence of increase in depressive symptoms as disease progresses (Lyketsos et al, 1996). The finding that incident major depressive episode was associated with more rapid decline in immune function (CD4+ lymphocyte count) is consistent with evidence that depressive symptoms are associated with more rapid progression of HIV disease (Ironson et al, 2005).…”
Section: Discussionsupporting
confidence: 71%
“…Additionally reliance on cross-sectional designs may be inherently unreliable, since risk of major depression may vary over the course of HIV infection, and may increase with onset of frank AIDS (Lyketsos et al, 1996). Finally, an extensive literature relates increased depression symptoms to stressful life events and diminished social support within the context of HIV infection (Evans et al, 1997;, Ironson et al, 2005, but whether this bears on risk of major depressive episodes is not known. Although past psychiatric history, HIV systemic and CNS disease, and life adversity are thought to be intertwined, they customarily have been studied separately rather than together.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, over half (53%) of the heterosexual migrants reported financial difficulties and 33% reported food privation through lack of money in the preceding month, compared to 21% and 7% of the other participants, respectively; social isolation, as defined by <1 weekly contact with family members/friends, concerned 20% of the heterosexual migrants versus 12% of the others (data available on request). Such adverse living conditions may have indirect effects on response to treatment through various pathways including poor adherence, high comorbidity (e.g., depression, tuberculosis, bacterial coinfections), inadequate healthcare, low social support, life event stress, or maladaptive coping [21,[28][29][30][31]. The low level of literacy of HIV-infected migrants [18] may further constitute a barrier to adequate access to care and HIV treatment adherence and knowledge, with consequences on health status [32,33].…”
Section: Differences In Treatment Failure Rates Across Subgroupsmentioning
confidence: 99%
“…Adjustment difficulties may also contribute to poor disease management [7,13]. Indeed, prior investigations have shown that heightened psychological distress is associated with accelerated disease progression as indicated by CD4 decline, increased viral load [13], and fewer natural killer cells [14].…”
mentioning
confidence: 99%